Pengaruh Pembelajaran Online “Google Meet” Terhadap Minat dan Motivasi Belajar Mahamahasiswa - Hamzah Robbani; Rendika Vhalery; Arsa Rachmania (FOCUS, 2022)
With the Covid-19 pandemic, students must learn to adapt. The application of e-learning is a form of learning adjustment in the midst of the Covid-19 pandemic. This learning is aimed at students' interest in learning and motivation to learn. To achieve this quality, students must of course have a lecturer role in learning, one of which is the use of appropriate and fun learning strategies, namely Google meet. Based on this statement, this study aims to examine and determine the effect of online learning "google meet" on student interest in learning and motivation to learn. This research is an associative research that uses a quantitative approach. This research was conducted at Unindra in April – May 2021. The research population was Unindra's economic education students. The sample used the non-probability section with purposive sampling technique which obtained 179 students as participants. The source of the data used in this research is the primary data source which is obtained directly. Data collection techniques using a questionnaire. The data analysis technique used regression test and hypothesis testing with the help of SPSS 24.0 program. for windows. The results of the study revealed that there was an effect of online learning "google meet" on student learning interest and there was an effect of online learning "google meet" on student learning motivation.